Response of the Diatom Phaeodactylum tricornutum to Photooxidative Stress Resulting from High Light Exposure - Domingues, Nuno; Matos, Ana Rita; Marques da Silva, Jorge; Cartaxana, Paulo (PLOS ONE, 2012)
The response of microalgae to photooxidative stress resulting from high light exposure is a well-studied phenomenon. However, direct analyses of photosystem II (PSII) D1 protein (the main target of photoinhibition) in diatoms are scarce. In this study, the response of the diatom model species Phaeodactylum tricornutum to short-term exposure to high light was examined and the levels of D1 protein determined immunochemically. Low light (LL) acclimated cells (40 µmol photons m−2 s−1) subjected to high light (HL, 1,250 µmol photons m−2 s−1) showed rapid induction of non-photochemical quenching (NPQ) and ca. 20-fold increase in diatoxanthin (DT) concentration. This resulted from the conversion of diadinoxanthin (DD) to DT through the activation of the DD-cycle. D1 protein levels under LL decreased about 30% after 1 h of the addition of lincomycin (LINC), a chloroplast protein synthesis inhibitor, showing significant D1 degradation and repair under low irradiance. Exposure to HL lead to a 3.2-fold increase in D1 degradation rate, whereas average D1 repair rate was 1.3-x higher under HL than LL, leading to decreased levels of D1 protein under HL. There were significant effects of both HL and LINC on P. tricornutum maximum quantum yield of PSII (Fv/Fm), showing a reduction of active PSII reaction centres. Partial recovery of Fv/Fm in the dark demonstrates the photosynthetic resilience of this diatom to changes in the light regime. P. tricornutum showed high allocation of total protein to D1 and an active D1-repair cycle to limit photoinhibition.